Contrasting human versus climatic impacts on erosion. Issue 16 (19th August 2015) - Cook, Timothy L.; Yellen, Brian C.; Woodruff, Jonathan D.; Miller, Daniel
Abstract: Both human activity and climate change can influence erosion rates and initiate rapid landscape change. Understanding the relative impact of these factors is critical to managing the risks of extreme erosion related to flooding and landslide occurrence. Here we present a 2100 year record of sediment mass accumulation and inferred erosion based on lacustrine sediment cores from Amherst Lake, Vermont, USA. Using deposition from August 2011 Tropical Storm Irene as a modern analogue, we identified distinct event deposits indicative of destructive erosion events. These deposits record a prolonged (multidecadal) interval of enhanced erosion following the initial storm‐induced landscape disturbance. The direct impact of human land cover alteration is minimal in comparison to the more recent twentieth century increase in the occurrence of catastrophic erosion linked to overall wetter conditions that favor high erosion rates and more easily trigger landslides during periods of extreme precipitation. Key Points: Tropical Storm Irene‐like flooding and erosion have occurred repeatedly Catastrophic erosion events result in persistent elevated sediment yields Climatically driven changes in twentieth century erosion exceeded human impacts